An overview and comparison of four sequence generating methods for robotic assembly. (6th May 2010) - Biswal, B.B.; Choudhury, B.B.; Mishra, D.; Dash, P.
The work presents an appropriate methodology for generation of assembly sequences. Several existing methods are studied and applied on randomly chosen products, which are then used as building blocks for development of a simplified and appropriate methodology for generation of robotic assembly sequences. The developed methodologies are validated logically. The suitability of these methods with respect to various aspects of robotic assembly is examined and the appropriate one is selected for use. The outcome of the present work is poised to make the robotic assembly system more efficient and more flexible.